Environmental & architectural phenomenology. Vol. 11, issue 1 - (:unkn) unknown (Kansas State University. Architecture Department, 2000)
Vol. 11, No. 1, Winter 2000 (includes “items of interest,” "citations received,” review essay of Steven Feld & Keith H. Basso's 1996 Senses of Place, chapter of Herb Childress's Landscapes of Betrayal, Landscapes of Joy, and the first part of a bibliography of environmental and architectural phenomenology).
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals